EXPERIMENTAL EVALUATION OF ANTICONVULSANT POTENTIALS OF OCIMUM GRATISSIMUM L. LEAF EXTRACTS - Ezike, A.; Okoli, C.; Agwagah, O. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Leaves of Ocimum gratissimum L. (Lamiaceae) are used in the traditional medicine of South-East Nigeria to manage seizures. This study was designed to evaluate the anticonvulsant and central depressant properties of the leaves. Dried powdered leaves of O. gratissimum were successively extracted using petroleum ether (40-60ºC) and methanol in a Soxhlet to afford PF and MF respectively, which were assessed for acute toxicity and lethality (LD50) (1) and phytochemical constituents (2,3). The anti-seizure properties of the extracts (200 and 400 mg/kg) were evaluated using pentylenetetrazol-induced seizure in mice. Also the central nervous system depressant activity was evaluated by assessing locomotor and anxiety activities using the open field model in mice. Data collected were analyzed using one way ANOVA and further subjected to LSD Post Hoc tests. The extracts significantly (P < 0.05) increased the time of onset of tonic and tonic-clonic seizures, and the time of death compared to control. In the open field study, the extract and fractions reduced the rate of grooming, rearing against a wall, centre square entries and line crossing. Oral LD50 was estimated to be greater than 5000 mg/kg. MF tested positive for alkaloids, while PF gave positive reactions to alkaloids, steroids, terpenes, saponins, flavonoids and others. The results suggest that the extracts of O. gratissimum offer protection against seizures and also depress the central nervous system; these attributes may contribute to the effectiveness of the plant in the management of seizures.